Apostolic tradition a new commentary - Bradshaw, Paul F. 1945- (Liturgical Press Academic, 2023)
"A commentary based on the 2011 Ethiopic text of the Apostolic Tradition of Hippolytus of Rome, suitable for beginner and scholar alike"--
Includes index
2301
Keywords: Hippolytus / Antipope / approximately 170-235 or 236 / Traditio apostolica; Canon law / Early church, ca. 30-600; Church history / Primitive and early church, ca. 30-600 / Sources